Modified boride, supported lithium supplementing agent and preparation method thereof and lithium metal battery without negative electrode
Patent Information
- Application Number
- CN202611479754.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的在于提供一种改性硼化物、负载型补锂剂及其制备方法与无负极锂金属电池,以解决或改善上述技术问题
本发明所提供改性硼化物由二维金属硼化物与锂化硼氧改性剂反应而得,锂化硼氧改性剂并非仅作为锂源存在,而是同时提供Li+和硼氧基团。一方面Li+能够与二维金属硼化物表面的M-O、B-O或缺陷氧位点发生配位,形成M-O-Li或B-O-Li型连接;另一方面,硼氧基团还能与二维金属硼化物表面的羟基(-OH)、氧端基(-O)或金属位点发生吸附、配位、硼氧基团交换或局部缩合,形成B-O-Li、Li-O-B或B-O-M型结构。由此,使二维金属硼化物由普通二维导电片层转化为具有锂硼氧亲和端基的界面桥接材料。该改性硼化物的主体结构仍为二维金属硼化物,其同时具备电子导通能力、锂离子亲和能力和界面配位能力,可作为后续补锂剂与正极材料之间的定域界面桥接材料。
Smart Images

Figure CN123002869A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more specifically, to a modified boride, a supported lithium supplement, a method for preparing the same, and a negative electrode-free lithium metal battery. Background Technology
[0002] Currently, electrodeless lithium metal batteries generally use bare copper current collectors instead of traditional graphite or excess lithium metal anodes. The anode is formed by the in-situ deposition of lithium extracted from the positive electrode during the first charge onto the copper foil. In other words, all the active lithium in the battery comes from the positive electrode material, which results in a huge loss of active lithium. Therefore, there is an urgent need for lithium replenishment agents in electrodeless lithium metal batteries.
[0003] Lithium replenishment in the positive electrode typically involves direct blending of a lithium replenishing agent. Specifically, the lithium replenishing agent is directly added to the active component slurry, and then homogenized with the active material, conductive agent, and binder before being coated onto the electrode sheet. This method is simple and easily compatible with existing positive electrode fabrication processes. However, the lithium replenishing agent is usually randomly distributed within the positive electrode active layer, which can easily lead to problems such as insufficient local electron contact, inadequate lithium delithiation, enhanced local side reactions, and fluctuations in lithium replenishment efficiency.
[0004] In addition, some technologies employ a coating method on the surface of the lithium replenishing agent, such as setting an oxide inner layer and a carbon outer layer on the lithium replenishing agent. This method can improve the performance of the lithium replenishing agent particles themselves, but it may also lead to problems such as increased resistance to lithium ion migration or increased lithium replenishment release potential.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a modified boride, a supported lithium supplement, a method for preparing the same, and a negative electrode-free lithium metal battery to solve or improve the above-mentioned technical problems.
[0007] This invention can be implemented as follows: In a first aspect, the present invention provides a modified boride, which is obtained by reacting a two-dimensional metal boride with a lithium boron oxide modifier; The mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:(0.01~0.3); Two-dimensional metal borides are two-dimensional sheet materials composed of transition metal elements and boron elements; The transition element M in the two-dimensional metal borides is Mo; the lithium boron oxide modifier is lithium bis(oxalato)borate.
[0008] In an optional embodiment, the mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:(0.08~0.15).
[0009] In an optional embodiment, the mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:0.1.
[0010] In an optional embodiment, the modified boride includes at least one of the following characteristics: Feature 1: The surface of the two-dimensional metal boride has at least one of surface end groups, intrinsic chemical bonds, and defect oxygen sites; wherein, the surface end groups include at least one of -O, -OH and -F, the intrinsic chemical bonds include at least one of BO and MO, and the M in MO corresponds to the metal element in the two-dimensional metal boride; Feature 2: The modified boride surface has at least one of BO-Li, MO-Li, -O and -OH, where M in MO-Li corresponds to the metal element in the two-dimensional metal boride.
[0011] Secondly, the present invention provides a method for preparing modified borides as described in the foregoing embodiments, comprising the following steps: adding a lithium boron oxide modifier to a two-dimensional metal boride dispersion, and reacting at 40°C to 70°C under a protective atmosphere for 4 to 8 hours.
[0012] In an optional embodiment, the reaction temperature is 50℃~60℃ and the reaction time is 5h~6h.
[0013] In an optional embodiment, the reaction is carried out under stirring conditions, with a stirring speed of 300 rpm to 800 rpm, more preferably 400 rpm to 600 rpm.
[0014] In an optional embodiment, the two-dimensional metal boride is mixed with a solvent at a solid-liquid ratio of 0.5 mg:1 mL to 2 mg:1 mL, and then dispersed to obtain a two-dimensional metal boride dispersion.
[0015] Thirdly, the present invention provides a supported lithium supplement, which is formed from a lithium supplement and the modified boride of the aforementioned embodiments; The coating rate of modified boride on the surface of lithium supplement is 5%~40%.
[0016] In an optional embodiment, the modified boride has a coating rate of 10% to 30% on the surface of the lithium supplement.
[0017] In an optional embodiment, the modified boride is locally adsorbed onto the surface of the lithium replenishing agent in a sheet-like, island-like, dot-like, or locally bridged manner.
[0018] In an optional embodiment, the lithium supplement includes at least one of Li5AlO4, Li2NiO2, Li2CuO2 and Li6CoO4.
[0019] In an optional implementation, the lithium supplement's D 50The range is 0.5μm to 3.0μm.
[0020] Fourthly, the present invention provides a method for preparing a supported lithium supplement as described in the foregoing embodiments, comprising the following steps: adding a dispersion of modified boride dropwise to a suspension of lithium supplement, followed by stirring; The mass ratio of lithium supplement to modified boride is 100:0.5 to 100:5.
[0021] In an optional embodiment, the mass ratio of lithium supplement to modified boride is 100:1 to 100:2.
[0022] In an optional embodiment, the stirring time is 30 min to 90 min, preferably 45 min to 60 min.
[0023] In an optional embodiment, the concentration of the modified boride dispersion is 0.2 mg / mL to 1 mg / mL.
[0024] Fifthly, the present invention provides a method for preparing a supported lithium replenishing agent as described in the foregoing embodiments, comprising the following steps: dry mechanically fusing the lithium replenishing agent with a modified boride in a dry environment with a dew point below -40°C; The mass ratio of lithium supplement to modified boride is 100:0.5 to 100:5.
[0025] In an optional embodiment, the mass ratio of lithium supplement to modified boride is 100:1 to 100:2.
[0026] In an optional embodiment, the dry mechanical fusion time is 5 min to 30 min, preferably 10 min to 20 min.
[0027] In an optional implementation, the processing temperature during the dry mechanical fusion process is ≤60°C, preferably ≤50°C.
[0028] In a sixth aspect, the present invention provides a modified cathode material, which is prepared by a cathode material and the supported lithium supplement agent of the aforementioned embodiments.
[0029] In an optional embodiment, the mass ratio of the cathode material to the lithium replenisher is 20:10 to 50:10.
[0030] In an optional embodiment, the mass ratio of the cathode material to the lithium replenisher is 30:10.
[0031] In a seventh aspect, the present invention provides a positive electrode sheet containing the modified positive electrode material of the aforementioned embodiments.
[0032] Eighthly, the present invention provides a negative electrode-free lithium metal battery, including the positive electrode sheet of the aforementioned embodiments.
[0033] The beneficial effects of this invention include: The modified boride provided by this invention is obtained by reacting a two-dimensional metal boride with a lithium boron oxide modifier. The lithium boron oxide modifier does not only exist as a lithium source, but also simultaneously provides Li. + And boron oxide groups. On the one hand, Li + It can coordinate with MO, BO, or defective oxygen sites on the surface of two-dimensional metal borides to form MO-Li or BO-Li type connections. On the other hand, the boron group can also adsorb, coordinate, exchange, or locally condense with hydroxyl (-OH), oxygen end groups (-O), or metal sites on the surface of two-dimensional metal borides to form BO-Li, Li-OB, or BOM type structures. Thus, the two-dimensional metal borides are transformed from ordinary two-dimensional conductive sheets into interfacial bridging materials with lithium boron-oxygen affinity end groups. The main structure of this modified boride remains a two-dimensional metal boride, which simultaneously possesses electronic conductivity, lithium-ion affinity, and interfacial coordination ability, and can be used as a localized interfacial bridging material between subsequent lithium supplementation agents and cathode materials.
[0034] Furthermore, the supported lithium replenisher provided by this invention, when subsequently mixed with the cathode material, allows the modified boride to act as a localized interface bridging material. One side or a localized region of the modified boride contacts the lithium replenisher particles, while the other side or edge further contacts the cathode material particles, thereby forming a ternary interface micro-cluster of lithium replenisher-modified boride-cathode material. This supported lithium replenisher can increase the probability of forming local electronic pathways around the lithium replenisher particles, reducing the problems of insufficient electron contact, inadequate lithium delithiation, and enhanced local side reactions in ordinary random mixing systems, thus contributing to improved battery electrochemical performance. Attached Figure Description
[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1 SEM image of the supported lithium supplement prepared in Example 1; Figure 2 The image shows a SEM image of the modified cathode material prepared in Example 1. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0038] The modified boride, supported lithium replenishing agent, and their preparation method, as well as the negative electrode-free lithium metal battery provided by this invention, will be described in detail below.
[0039] Modified borides The present invention provides a modified boride obtained by reacting a two-dimensional metal boride with a lithium boron oxide modifier.
[0040] In some optional embodiments, the mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier can be 1:(0.01~0.3), such as 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, or 1:0.3, or other values within the range of 1:(0.01~0.3). In some more preferred embodiments, the mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:(0.08~0.15). In some even more preferred embodiments, the mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:0.1.
[0041] If the amount of lithium boron oxide modifier is too small, it will not be conducive to the formation of sufficient lithium boron oxide affinity end groups on the surface of two-dimensional metal borides, resulting in insufficient interfacial bonding ability between them and lithium supplementation agents and cathode materials. If the amount of lithium boron oxide modifier is too large, it may lead to the formation of excessive boron oxide species or residual lithium salts on the surface of two-dimensional metal borides, increasing the risk of sheet aggregation and affecting the electron transport capability of the main structure of two-dimensional metal borides.
[0042] In some alternative embodiments, the two-dimensional metal boride is a two-dimensional sheet material composed of a transition metal element and boron. The transition metal M may, exemplarily, include at least one of Mo, V, Cr, and Ti.
[0043] In some optional embodiments, the surface of the two-dimensional metal boride has at least one of surface end groups, intrinsic chemical bonds, and defect oxygen sites; wherein the surface end groups include at least one of -O, -OH, and -F, and the intrinsic chemical bonds include at least one of BO and MO, where M in MO corresponds to a metal element in the two-dimensional metal boride. The aforementioned end groups or defect sites can serve as binding sites for subsequent lithiation boron oxide terminalization reactions.
[0044] In some alternative embodiments, two-dimensional metal borides (MBene) can be prepared as follows: (1) Preparation of precursor: According to the molecular formula of the two-dimensional metal boride, M powder (purity ≥99.5%), aluminum powder (purity ≥99.5%) and boron powder (purity ≥99.5%) were weighed according to the preset molar ratio and placed in a zirconia ball mill jar. Anhydrous ethanol was used as the ball milling medium, and the ball-to-material ratio was controlled at 8:1 to 12:1. The mixture was ball milled for 8h to 12h at a ball milling speed of 300rpm to 400rpm. After ball milling, the solvent was removed by vacuum drying at 75℃ to 85℃. The resulting mixed powder was pressed into blocks and heated to 1500℃ to 1600℃ at 4℃ / min to 6℃ / min under the protection of high-purity argon gas and held for 2h to 4h. Then, it was cooled to room temperature with the furnace. The sintered blocks were crushed and sieved to obtain the precursor.
[0045] (2) Preparation of two-dimensional metal borides Weigh 1.0 g of the precursor and slowly add it to an etching solution prepared by dissolving 1.0 g of LiF in 20 mL of 8.5 mol / L to 9.5 mol / L hydrochloric acid. Stir and react at 32°C to 38°C for 45 to 50 hours to selectively remove the Al layer. After the reaction, repeatedly centrifuge and wash with deionized water until the pH of the supernatant is approximately 6 to 7. Then add deionized water and ultrasonically peel under argon protection for 30 to 60 minutes, followed by centrifugation at 3200 to 3800 rpm for 8 to 12 minutes. Collect the supernatant. Freeze-dry to obtain two-dimensional metal boride powder. In some optional embodiments, the lithium boron oxide modifier may, by way of example but not limitation, include at least one of lithium bis(oxalato)borate, lithium metaborate, lithium borate, and lithium tetraborate. In some more preferred embodiments, the lithium boron oxide modifier includes lithium bis(oxalato)borate.
[0046] In some alternative embodiments, the modified boride surface has at least one of BO-Li, MO-Li, -O, and -OH, where M in MO-Li corresponds to a metal element in the two-dimensional metal boride. After lithium boron oxide modification, the surface of the two-dimensional metal boride at least partially introduces or transforms to form the aforementioned end groups or chemical bonds.
[0047] Accordingly, the present invention also provides a method for preparing the modified boride as described above, comprising the following steps: adding a lithium boron oxide modifier to a two-dimensional metal boride dispersion, and reacting at 40°C to 70°C under a protective atmosphere for 4 to 8 hours.
[0048] The reaction temperature can be 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, or 70℃, or other values within the range of 40℃ to 70℃. The reaction time can be 4h, 5h, 6h, 7h, or 8h, or other values within the range of 4h to 8h. In some preferred embodiments, the reaction temperature is 50℃ to 60℃, and the reaction time is 5h to 6h.
[0049] If the reaction temperature is below 40℃, it is not conducive to the full coordination and binding between lithium ions and oxygen end groups and defect sites on the surface of two-dimensional metal borides, resulting in insufficient introduction of oxygen end groups into lithiboride. If the reaction temperature is above 70℃, it may promote the destruction of the two-dimensional metal boride sheet structure or excessive reaction of end groups, while increasing the probability of side reactions.
[0050] The protective atmosphere mentioned above may include a nitrogen atmosphere or an argon atmosphere, etc.
[0051] The above reaction can be carried out under stirring conditions, and the stirring speed can be 300 rpm to 800 rpm, such as 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, or 800 rpm, or other values within the range of 300 rpm to 800 rpm. Preferably, the stirring speed can be 400 rpm to 600 rpm.
[0052] In some alternative embodiments, the two-dimensional metal borides can be pre-treated by vacuum drying. For example, the two-dimensional metal borides can be dried under vacuum conditions of 80°C to 120°C for 6 to 12 hours to remove adsorbed water and low-boiling-point impurities from their surface, thereby reducing the risk of hydrolysis, side reactions, and lamellar aggregation during the subsequent lithiation of boron oxides.
[0053] In some alternative embodiments, the two-dimensional metal boride dispersion can be obtained by mixing the two-dimensional metal boride with a solvent at a solid-liquid ratio of 0.5 mg:1 mL to 2 mg:1 mL, and then dispersing it.
[0054] The solid-liquid ratio of the two-dimensional metal boride to the solvent can be 0.5 mg:1 mL, 1 mg:1 mL, 1.5 mg:1 mL, or 2 mg:1 mL, or other values within the range of 0.5 mg:1 mL to 2 mg:1 mL. The solvent may, by example but not in a limited sense, include anhydrous ethanol and acetonitrile in a volume ratio of 1:1.
[0055] The above dispersion methods may include ultrasonic dispersion and / or stirring dispersion. The ultrasonic time can be 5 min to 15 min, such as 5 min, 10 min, or 15 min, or other values within the range of 5 min to 15 min. Stirring dispersion can be carried out at 1000 rpm to 2000 rpm for 10 min to 20 min to ensure that the two-dimensional metal boride is fully wetted and dispersed in the solvent.
[0056] After the reaction is complete, the mixture is centrifuged or filtered to collect the solid product. It is then washed 2-3 times with anhydrous ethanol to remove unbound free lithium boron oxide modifier and soluble byproducts, preventing the free lithium salt from acting as an independent additive in the subsequent electrode system. The washed solid can be dried under vacuum at 60℃-90℃ for 6-12 hours. Preferably, it is dried under vacuum at 80℃ for 8 hours to obtain the modified boride.
[0057] In the preparation process of the above-mentioned modified borides, the lithium boron oxide modifier does not only exist as a lithium source, but also provides Li. + And boron oxide groups. On the one hand, Li + It can coordinate with MO, BO, or defective oxygen sites on the surface of two-dimensional metal borides to form MO-Li or BO-Li type connections. On the other hand, the boron group can also adsorb, coordinate, exchange, or locally condense with hydroxyl (-OH), oxygen end groups (-O), or metal sites on the surface of two-dimensional metal borides to form BO-Li, Li-OB, or BOM type end group structures. Thus, two-dimensional metal borides are transformed from ordinary two-dimensional conductive sheets into interfacial bridging materials with lithium boron oxygen affinity end groups.
[0058] It is important to emphasize that the lithium boron oxide end-grouping treatment in this invention does not form a continuous borate coating layer, nor does it destroy the main framework of the two-dimensional metal boride. Instead, it constructs discontinuous lithium boron oxide end-group sites on the surface of the two-dimensional metal boride. These end-groups can undergo lithium-ion bridging, Lewis acid-base coordination, hydrogen bonding, and van der Waals adhesion with Li-O, Al-O, Al-OH, or residual lithium salt sites on the surface of the lithium replenishing agent in subsequent steps, thereby improving the localized adsorption capacity of the two-dimensional metal boride on the surface of the lithium replenishing agent particles.
[0059] Continuing from the above, the main structure of the modified boride prepared by this invention remains a two-dimensional metal boride, with end groups and chemical bonds such as BO-Li, MO-Li, Li-OB, -OH, and / or -O on its surface. These end groups and chemical bonds can be characterized by XPS, FTIR, Raman, or ToF-SIMS. Changes in the spectral peaks of B 1s, Li 1s, O 1s, and the corresponding metal elements can be used to demonstrate the introduction of lithium-boron-oxygen end groups. Through the above-mentioned lithium-boron-oxygen end-grouping treatment, the modified boride simultaneously possesses electronic conductivity, lithium-ion affinity, and interfacial coordination ability, and can serve as a localized interfacial bridging material between subsequent lithium supplementation agents and cathode materials.
[0060]
Lithium-supported additives
[0061] In some optional embodiments, the coating rate of the modified boride on the surface of the lithium replenisher can be 5% to 40%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40%, or other values within the range of 5% to 40%. In some preferred embodiments, the coating rate of the modified boride on the surface of the lithium replenisher can be 10% to 30%. The above coating rates can be obtained statistically by SEM, TEM, or elemental surface scan images. Specifically, no less than 50, preferably no less than 100, lithium replenisher particles can be selected, and the proportion of the coverage area of the modified boride on the projected surface of a single lithium replenisher particle to the projected area of that particle can be statistically analyzed to obtain the coating rate of a single particle. The local distribution of the modified boride on the surface of the lithium replenisher particles can also be confirmed by EDS surface scan signals of characteristic elements of two-dimensional metal borides such as Mo, V, Cr, Ti, or B.
[0062] In this invention, the aforementioned coating rate range of 5% to 40% indicates that the modified boride is locally adsorbed on the surface of the lithium supplement in a discontinuous manner, primarily through asymmetric and incomplete coating. When the coating rate of the modified boride on the lithium supplement surface is less than 5%, the number of two-dimensional metal borides on the surface of the lithium supplement particles is insufficient, making it difficult to form effective electronic bridging and interface stabilization. When the coating rate of the modified boride on the surface of the lithium supplement surface is greater than 40%, the two-dimensional metal borides may form a continuous or quasi-continuous coating layer, increasing the Li-24 ratio. + Migration resistance affects the delithiation and release of lithium by the lithium supplement. Therefore, controlling the coating rate at 5%–40%, especially 10%–30%, can achieve a balance between electron transport and lithium-ion release.
[0063] In some alternative embodiments, the modified boride is localized and adsorbed onto the surface of the lithium supplement in a sheet-like, island-like, dot-like, or locally bridged manner.
[0064] In some alternative embodiments, the lithium supplement may, by way of example but not limitation, include at least one of Li5AlO4, Li2NiO2, Li2CuO2 and Li6CoO4.
[0065] Taking Li5AlO4 as an example of a lithium supplement, it can be prepared as follows: A lithium source and an aluminum source are ball-milled to obtain a uniformly mixed slurry. The ball-milled slurry is then vacuum-dried to obtain a precursor powder. The precursor powder is then heat-treated, followed by grinding and sieving.
[0066] The molar ratio of Li in the lithium source to Al in the aluminum source can be from 5.05:1 to 5.30:1, such as 5.05:1, 5.10:1, 5.15:1, 5.20:1, 5.25:1, or 5.30:1, or other values within the range of 5.05:1 to 5.30:1. In some preferred embodiments, the molar ratio of Li in the lithium source to Al in the aluminum source can be 5.20:1. The lithium source may exemplary include LiOH·H2O, and the aluminum source may exemplary include Al(OH)3.
[0067] The ball milling process can be carried out in a zirconia ball milling jar. The ball milling medium can be anhydrous ethanol, the ball-to-material ratio can be 5:1 to 10:1, the ball milling speed can be 300 rpm to 500 rpm, and the ball milling time can be 4 h to 8 h.
[0068] The temperature for vacuum drying can be 75℃~85℃, and the drying time can be 8h~12h.
[0069] The heat treatment can be carried out under a dry argon or dry oxygen atmosphere. The heat treatment process can begin by heating to 350℃~450℃ at a rate of 2℃ / min~5℃ / min and holding for 3h~5h; then heating to 650℃~760℃ and holding for 4h~8h. After cooling to room temperature in the furnace, the mixture is ground and sieved to obtain Li5AlO4 lithium supplement.
[0070] In some alternative implementations, the D of the lithium supplement 50 The thickness can be 0.5μm to 3.0μm, preferably 1.0μm to 2.0μm.
[0071] Furthermore, the prepared Li5AlO4 powder can be vacuum dried at 115℃~125℃ for 4h~8h and then transferred to a dry environment with a dew point below -40℃ for storage.
[0072] Accordingly, the present invention also provides a method for preparing the above-mentioned supported lithium supplement, which can be prepared by wet heterogeneous adsorption or dry mechanical fusion.
[0073] In this invention, the wet heterogeneous adsorption method may include the following steps: adding a dispersion of modified boride dropwise to a suspension of lithium supplementation agent, followed by stirring.
[0074] It should be noted that in the above preparation process, the specific order in which the modified boride dispersion is added dropwise to the lithium supplement agent suspension is beneficial for the modified boride to gradually contact the surface of the lithium supplement agent particles after entering the system, promoting heterogeneous adsorption and reducing the possibility of the modified boride agglomerating or randomly dispersing in the slurry. If the lithium supplement agent is added to the modified boride dispersion all at once, the two-dimensional metal boride sheets are more likely to agglomerate first, which is not conducive to the formation of a uniform local pre-adsorption structure.
[0075] The mass ratio of the lithium supplement to the modified boride can be from 100:0.5 to 100:5, such as 100:0.5, 100:1, 100:2, 100:3, 100:4, or 100:5, or other values within the range of 100:0.5 to 100:5. In some preferred embodiments, the mass ratio of the lithium supplement to the modified boride is from 100:1 to 100:2.
[0076] The mass ratio of lithium replenishing agent to modified boride is crucial for forming a discontinuous pre-adsorption structure. When the amount of modified boride added is too low, the number of contact points formed on the lithium replenishing agent surface is insufficient, making it difficult to form effective interfacial bridging during subsequent composite with ternary cathode materials. When the amount of modified boride added is too high, it easily forms a continuous or quasi-continuous coating layer on the lithium replenishing agent particle surface, or forms lamellar agglomerates in the slurry, potentially hindering lithium release during the first charging process. Therefore, by controlling the addition ratio of modified boride, a discontinuous, localized, and bridging pre-adsorption structure can be formed on the lithium replenishing agent surface.
[0077] The stirring time can be 30 min to 90 min, preferably 45 min to 60 min.
[0078] In some optional embodiments, under stirring conditions of 300 rpm to 800 rpm, the dispersion of modified boride is added dropwise to the suspension of lithium supplementation agent at a preset amount. After the addition is completed, stirring is continued for 30 min to 90 min under a dry nitrogen or argon atmosphere, so that the modified boride is localized and adsorbed on the surface of lithium supplementation agent particles in the form of plates, islands, dots or local bridging, to obtain a supported lithium supplementation agent.
[0079] In some optional embodiments, the modified boride dispersion can be prepared as follows: In a drying room or inert atmosphere glove box, the modified boride is added to anhydrous NMP to prepare a two-dimensional metal boride dispersion. The concentration of the modified boride dispersion can be 0.2 mg / mL to 1 mg / mL, such as 0.2 mg / mL, 0.5 mg / mL, 0.8 mg / mL, or 1 mg / mL, or other values within the range of 0.2 mg / mL to 1 mg / mL. In some preferred embodiments, the concentration of the modified boride dispersion can be 0.3 mg / mL to 0.6 mg / mL. The dispersion method can be ultrasonic treatment for 5 min to 15 min, or high-speed dispersion at 1000 rpm to 2000 rpm for 10 min to 20 min, to ensure that the modified boride is fully wetted and dispersed in anhydrous NMP.
[0080] In some alternative embodiments, the suspension of the lithium replenishing agent can be prepared as follows: the lithium replenishing agent is added to anhydrous NMP under dry nitrogen or argon protection to avoid surface side reactions caused by contact between the lithium replenishing agent and moisture or carbon dioxide in the air.
[0081] In the aforementioned wet heterogeneous adsorption process, the BO-Li, MO-Li, Li-OB, -O, and -OH end groups on the modified boride surface can undergo lithium-ion bridging, Lewis acid-base coordination, hydrogen bonding, and van der Waals interactions with the Li-O, Al-O, Al-OH, or residual lithium salt sites on the lithium supplementer surface. Consequently, the modified boride no longer functions as a random dispersion of ordinary two-dimensional conductive agents in the slurry system, but preferentially adsorbs onto polar sites, defect sites, or high surface energy sites on the lithium supplementer particle surface, forming a pre-adsorption structure with localized interfacial bonding.
[0082] In this invention, the dry mechanical fusion method may include the following steps: dry mechanical fusion of lithium replenishing agent and modified boride in a dry environment with a dew point below -40°C.
[0083] The mass ratio of the lithium supplement to the modified boride can be from 100:0.5 to 100:5, such as 100:0.5, 100:1, 100:2, 100:3, 100:4, or 100:5, or other values within the range of 100:0.5 to 100:5. In some preferred embodiments, the mass ratio of the lithium supplement to the modified boride is from 100:1 to 100:2.
[0084] The dry mechanical fusion time can be 5 min to 30 min, such as 5 min, 10 min, 20 min, or 30 min, or other values within the range of 5 min to 30 min. In some preferred embodiments, the dry mechanical fusion time is 10 min to 20 min.
[0085] In the above-mentioned dry mechanical fusion process, the processing temperature is ≤60℃, preferably ≤50℃.
[0086] In some alternative embodiments, the dried lithium supplement and modified boride are premixed at a predetermined mass ratio in a dry environment with a dew point below -40°C. The premixed powder is then placed in a mechanical fusion machine, a high-speed shear mixer, a planetary low-energy ball mill, or an airflow-assisted dry coating device and treated for 5 to 30 minutes under nitrogen or argon protection, with the treatment temperature controlled not to exceed 60°C.
[0087] In the aforementioned dry mechanical fusion process, the modified boride comes into contact with the surface of the lithium replenishing agent particles under mechanical shearing, collision, and pressure. Through the BO-Li, MO-Li, Li-OB, -O, and -OH end groups on its surface, it forms lithium-ion bridges, coordinate adsorption, and hydrogen bonds with the Li-O, Al-O, or Al-OH sites on the lithium replenishing agent surface, thereby fixing it to the lithium replenishing agent surface. This method requires no large amount of solvent, reduces the chance of the lithium replenishing agent coming into contact with moisture or residual solvent, and more easily yields discontinuous pre-adsorption structures in the form of sheets, islands, dots, or locally bridged structures.
[0088] Building upon the above, this invention utilizes a supported lithium replenisher obtained through wet heterogeneous adsorption or dry mechanical fusion. When subsequently mixed with the cathode material, the modified boride acts as a localized interface bridging material, contacting the lithium replenisher particles on one side or in a localized area, while further contacting the cathode material particles on the other side or at the edge, thus forming a ternary interface micro-cluster of lithium replenisher-modified boride-cathode material. This supported lithium replenisher increases the probability of forming local electronic pathways around the lithium replenisher particles, reducing the problems of insufficient electron contact, inadequate delithiation, and enhanced local side reactions in ordinary random mixing systems.
[0089] Modified cathode materials The present invention also provides a modified cathode material, which is prepared by a cathode material and the above-mentioned supported lithium supplement agent.
[0090] In some optional embodiments, the mass ratio of the cathode material to the lithium supplement in the supported lithium supplement can be from 20:10 to 50:10, such as 20:10, 30:10, 40:10, or 50:10, or other values within the range of 20:10 to 50:10. In some preferred embodiments, the mass ratio of the cathode material to the lithium supplement is 30:10.
[0091] In some alternative implementations, the cathode material may, by way of example but not by way of limitation, include nickel-cobalt-manganese (NCM) ternary cathode material and / or nickel-cobalt-manganese-aluminum (NCMA) cathode material, etc.
[0092] In this modified cathode material, the lithium replenisher is used to release active lithium during the first charge; the modified boride acts as a localized interface bridge, with its surface end groups used to connect the lithium replenisher particles and cathode material particles through lithium-ion bridging, Lewis acid-base coordination, hydrogen bonding, and / or van der Waals adhesion, providing local electronic pathways and interface stabilization; the cathode material, as the main lithium storage active material, provides the main reversible capacity. These three components, through lithium-boron-oxygen end-grouping, lithium replenisher pre-adsorption, and secondary composite formation of the cathode material, form a localized composite contact unit, which is beneficial for improving the battery's electrochemical performance.
[0093] In some more specific embodiments, under a dry nitrogen or argon atmosphere, the cathode material and the supported lithium supplement are stirred at a low speed of 300 rpm to 600 rpm (e.g., 300 rpm, 400 rpm, 500 rpm, or 600 rpm) for 30 min to 60 min (e.g., 30 min, 40 min, 50 min, or 60 min) to ensure that the cathode material particles and the supported lithium supplement are in full contact, while avoiding damage to the structure of the supported lithium supplement.
[0094] In the above process, the modified borides, which have been locally adsorbed on the surface of the lithium replenisher, can further interact with Li-O, Ni-O, Co-O, Mn-O, Al-O, or hydroxylation sites on the surface of the cathode material through their exposed lamellar regions, edge regions, or surface end groups. This interaction involves lithium-ion bridging, Lewis acid-base coordination, hydrogen bonding, and van der Waals adhesion, resulting in at least a partial location of the two-dimensional metal borides between the lithium replenisher particles and the cathode material particles, forming localized ternary interface microclusters. These ternary interface microclusters can be characterized by SEM, TEM, STEM-EDS, EDS surface scanning, or line scanning.
[0095] It should be noted that in this invention, the lithium replenishing agent, modified boride, and cathode material are not randomly mixed all at once. Instead, the lithium replenishing agent and modified boride are first combined to form a supported lithium replenishing agent, which is then introduced into the cathode material for secondary composite formation. This construction sequence increases the probability of local enrichment of the modified boride around the lithium replenishing agent particles and increases its probability of bridging the lithium replenishing agent and the cathode material.
[0096]
Positive Electrode
[0097] In some alternative embodiments, the areal density of the positive electrode sheet on one side can be 18 mg / cm³. 2 ~22mg / cm 2 .
[0098] In some alternative implementations, the active layer thickness of the positive electrode can be 55 μm to 75 μm.
[0099] In some alternative embodiments, the compaction density of the positive electrode sheet can be 3.30 g / cm³. 3 ~3.60g / cm 3 .
[0100] In some alternative implementations, the porosity of the positive electrode can be 25% to 35%.
[0101] In some alternative embodiments, the positive electrode sheet is obtained by coating a positive electrode active slurry onto a positive electrode current collector, followed by drying and rolling.
[0102] The positive current collector mentioned above can be aluminum foil with a thickness of 15 μm.
[0103] The aforementioned positive electrode active slurry includes the modified positive electrode material, and also includes conductive agents, binders, and solvents. The conductive agent may, for example, include at least one of SP, CNT, acetylene black, conductive graphite, and graphene; the binder may, for example, include PVDF; and the solvent may, for example, include NMP.
[0104] The solid content of the positive electrode active slurry can be 58%~72%, and the viscosity can be controlled between 3000 mPa·s and 9000 mPa·s. The amounts of conductive agent and binder can be set according to conventional ranges.
[0105] In some optional embodiments, drying can be performed first by hot air drying at 55°C to 65°C for 5 min to 10 min, followed by drying at 85°C to 95°C for 10 min to 20 min to remove the main solvent; then by vacuum drying at 110°C to 120°C for 8 h to 12 h to remove residual solvent, thus obtaining a dried electrode.
[0106] In some alternative implementations, the rolling temperature can be 50°C to 80°C, and the linear pressure can be 80 N / cm to 180 N / cm.
[0107]
Battery
[0108] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0109] The lithium hydroxide monohydrate (LiOH·H2O) used in the following examples was purchased from Aladdin Reagent Co., Ltd. (purity 99%); aluminum hydroxide (Al(OH)3) was purchased from Sinopharm Chemical Reagent Co., Ltd. (analytical grade); lithium bis(oxalateborate) borate (LiBOB) was purchased from Sigma-Aldrich (model 933716, battery grade, purity ≥99.9%); anhydrous ethanol, acetonitrile, and N-methylpyrrolidone (NMP) were all analytical grade.
[0110] Mo 4 / 3 B2T x Two-dimensional metal borides were prepared as follows: Molybdenum powder (purity ≥99.5%), aluminum powder (purity ≥99.5%), and boron powder (purity ≥99.5%) were weighed in a zirconia ball mill jar with a molar ratio of Mo:Al:B = (4 / 3):1:2. The mixture was placed in the jar and ball-milled for 10 hours at a ball milling speed of 350 rpm using anhydrous ethanol as the milling medium and a ball-to-powder ratio of 10:1. After milling, the solvent was removed by vacuum drying at 80 °C. The resulting mixed powder was pressed into a block and heated to 1550 °C at a rate of 5 °C / min for 3 hours under high-purity argon protection, followed by furnace cooling to room temperature. The sintered block was pulverized and sieved to obtain the precursor. 1.0 g of the precursor was weighed and slowly added to an etching solution prepared by dissolving 1.0 g of LiF in 20 mL of 9 mol / L hydrochloric acid. The mixture was stirred at 35 °C for 48 hours to selectively remove the Al layer. After the reaction, the supernatant was repeatedly washed by centrifugation with deionized water until the pH of the supernatant was approximately 6-7. Then, deionized water was added, and the mixture was ultrasonically exfoliated for 45 min under argon protection, followed by centrifugation at 3500 rpm for 10 min. The supernatant was collected and freeze-dried to obtain two-dimensional metal boride powder.
[0111] The Mo2BTx two-dimensional metal boride was prepared using the same method as described above, except that the molar ratio Mo:Al:B was 2:1:1 during the precursor preparation process.
[0112] Example 1 This embodiment provides a positive electrode sheet, the preparation method of which includes: S1: Preparation of lithium supplement.
[0113] LiOH·H2O and Al(OH)3 were mixed and ball-milled in a zirconia ball mill jar at a Li:Al molar ratio of 5.20:1. Anhydrous ethanol was used as the milling medium, the milling speed was 400 rpm, and the milling time was 6 h. After milling, the mixture was vacuum-dried at 80 °C for 10 h to obtain the precursor powder. The precursor powder was then heated to 420 °C at a rate of 3 °C / min and held for 4 h, followed by heating to 720 °C and holding for 6 h. The mixture was then cooled to room temperature in the furnace, ground, and sieved to obtain D. 50 It is a lithium supplement for 1.6 μm Li5AlO4.
[0114] S2: Preparation of modified borides.
[0115] Put 1.0g Mo 4 / 3 B2T x Two-dimensional metal borides were added to 1 mL of a mixed solvent (anhydrous ethanol and acetonitrile in a 1:1 volume ratio) to obtain a dispersion of the two-dimensional metal borides. 0.10 g of lithium bis(oxalato)borate was added to the dispersion, and the mixture was stirred at 500 rpm for 6 h at 60 °C under an argon atmosphere. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 80 °C for 8 h to obtain the modified boride.
[0116] S3: Preparation of supported lithium supplements (such as...) Figure 1 (As shown).
[0117] Under a dry nitrogen atmosphere, the modified boride was added to anhydrous NMP and dispersed at 1500 rpm for 15 min to obtain a modified boride dispersion. The concentration of the modified boride dispersion was 0.5 mg / mL.
[0118] Under a dry nitrogen atmosphere, the lithium supplement was added to anhydrous NMP to obtain a suspension of the lithium supplement. The concentration of the lithium supplement suspension was 20 mg / mL.
[0119] Under stirring at 500 rpm, the modified boride dispersion was slowly added dropwise to the lithium supplement agent suspension, maintaining a mass ratio of modified boride to lithium supplement agent of 1.5:100. After the addition was complete, stirring was continued at 500 rpm for 60 min to obtain a supported lithium supplement agent slurry. In the obtained supported lithium supplement agent, the modified boride was discontinuously adsorbed onto the surface of the lithium supplement agent particles, with the coating rate of modified boride on the surface of a single lithium supplement agent particle being approximately 20%.
[0120] S4: Preparation of modified cathode materials (such as...) Figure 2 (As shown).
[0121] The NCM811 ternary cathode material was added to the above-mentioned supported lithium supplement slurry at a mass ratio of 30:10 to ternary cathode material and lithium supplement agent. Then, the mixture was stirred at a low speed of 450 rpm for 45 min under a dry nitrogen atmosphere to obtain the modified cathode material.
[0122] S5: Prepare the positive electrode sheet.
[0123] A modified cathode material, a conductive agent (CNT), a binder (PVDF), and a solvent (NMP) were mixed to obtain a cathode active slurry with a solid content of 68% and a viscosity of 6500 mPa·s. The mass ratio of the modified cathode material, the conductive agent, and the binder was 97.0:1.0:2.0.
[0124] The positive electrode active slurry was coated onto the surface of an aluminum foil with a thickness of 15 μm, and then dried sequentially at 60℃ for 8 min, 90℃ for 15 min, and 120℃ under vacuum for 10 h. Subsequently, it was gently rolled at 60℃ and 100 N / cm to obtain the positive electrode sheet.
[0125] The surface density of a single surface is 20.5 mg / cm³. 2 The active layer thickness is 65 μm, the lithium supplementation content in the positive electrode is 2.0%, the porosity is 30%, and the compaction density is 3.45 g / cm³. 3 .
[0126] Example 2 The difference between this embodiment and Embodiment 1 is that the preparation method of S3 is different, as detailed below: The dried lithium supplement and modified boride were premixed in a dry environment with a dew point of -40°C, wherein the mass ratio of modified boride to lithium supplement was 1.5:100. The premixed powder was then placed in a mechanical fusion machine and treated at 800 rpm for 15 min under nitrogen protection, with the treatment temperature controlled not to exceed 50°C, to obtain the supported lithium supplement.
[0127] Example 3 The difference between this embodiment and Embodiment 1 is that the mass ratio of lithium supplement to modified boride is 100:0.5.
[0128] Example 4 The difference between this embodiment and Embodiment 1 is that the mass ratio of lithium supplement to modified boride is 100:3.
[0129] Example 5 The difference between this embodiment and Embodiment 1 is that: Mo 4 / 3 B2T x Two-dimensional metal borides are replaced by an equal amount of Mo2BT x Two-dimensional metal borides, the remaining steps are the same as in Example 1.
[0130] Example 6 The difference between this embodiment and Embodiment 1 is that the cathode material is replaced in equal amounts with NCM90 (LiNi). 0.9 Co 0.05 Mn 0.05 O2).
[0131] Example 7 This embodiment provides a positive electrode sheet, the preparation method of which includes: S1: Preparation of lithium supplement.
[0132] LiOH·H2O and Al(OH)3 were mixed and ball-milled in a zirconia ball mill jar at a Li:Al molar ratio of 5.05:1. The ball milling medium was anhydrous ethanol, the milling speed was 300 rpm, and the milling time was 8 h. After milling, the mixture was vacuum-dried at 75 °C for 12 h to obtain precursor powder. The precursor powder was then heated to 350 °C at a rate of 2 °C / min and held for 5 h, followed by heating to 650 °C and holding for 8 h. The mixture was then cooled to room temperature in the furnace, ground, and sieved to obtain D. 50 It is a lithium supplement for 1.8μm Li5AlO4.
[0133] S2: Preparation of modified borides.
[0134] Put 1.0g Mo 4 / 3 B2T x Two-dimensional metal borides were added to 5 mL of a mixed solvent (anhydrous ethanol and acetonitrile in a 1:1 volume ratio) to obtain a dispersion of the two-dimensional metal borides. 0.08 g of lithium bis(oxalato)borate was added to the dispersion, and the mixture was stirred at 300 rpm for 6 h at 50 °C under an argon atmosphere. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60 °C for 12 h to obtain the modified boride.
[0135] S3: Preparation of supported lithium supplement.
[0136] Under a dry nitrogen atmosphere, the modified boride was added to anhydrous NMP and dispersed at 1000 rpm for 20 min to obtain a modified boride dispersion. The concentration of the modified boride dispersion was 0.2 mg / mL.
[0137] Under a dry nitrogen atmosphere, the lithium supplement was added to anhydrous NMP to obtain a suspension of the lithium supplement. The concentration of the lithium supplement suspension was 15 mg / mL.
[0138] Under stirring at 500 rpm, the modified boride dispersion was slowly added dropwise to the lithium supplement agent suspension, maintaining a mass ratio of modified boride to lithium supplement agent of 0.5:100. After the addition was complete, stirring was continued at 500 rpm for 90 min to obtain a supported lithium supplement agent slurry. In the obtained supported lithium supplement agent, the modified boride was discontinuously adsorbed onto the surface of the lithium supplement agent particles, with a coating rate of approximately 12% of the modified boride on the surface of a single lithium supplement agent particle.
[0139] S4: Prepare modified cathode materials.
[0140] The NCM811 ternary cathode material was added to the above-mentioned supported lithium supplement slurry at a mass ratio of 20:10 to ternary cathode material. Then, the mixture was stirred at a low speed of 300 rpm for 60 min under a dry nitrogen atmosphere to obtain the modified cathode material.
[0141] S5: Prepare the positive electrode sheet.
[0142] A positive electrode active slurry with a solid content of 65% and a viscosity of 5200 mPa·s is prepared by mixing modified positive electrode material, conductive agent (CNT), binder (PVDF), and solvent (NMP). The mass ratio of modified positive electrode material, conductive agent, and binder is 97.0:1.0:2.0.
[0143] The positive electrode active slurry was coated onto the surface of aluminum foil and dried sequentially at 55℃ for 10 min, 85℃ for 20 min, and 110℃ under vacuum for 12 h. Then, it was gently rolled at 50℃ and 80 N / cm to obtain the positive electrode sheet.
[0144] Example 8 This embodiment provides a positive electrode sheet, the preparation method of which includes: S1: Preparation of lithium supplement.
[0145] LiOH·H2O and Al(OH)3 were mixed and ball-milled in a zirconia ball mill jar at a Li:Al molar ratio of 5.30:1. The ball milling medium was anhydrous ethanol, the milling speed was 500 rpm, and the milling time was 4 h. After milling, the mixture was vacuum-dried at 85 °C for 8 h to obtain the precursor powder. The precursor powder was then heated to 450 °C at a rate of 5 °C / min and held for 3 h, followed by heating to 760 °C and holding for 4 h. It was then cooled to room temperature in the furnace, ground, and sieved to obtain D. 50 It is a lithium supplement for 1.3μm Li5AlO4.
[0146] S2: Preparation of modified borides.
[0147] Put 1.0g Mo 4 / 3 B2T x Two-dimensional metal borides were added to 2 mL of a mixed solvent (anhydrous ethanol and acetonitrile in a 1:1 volume ratio) to obtain a dispersion of the two-dimensional metal borides. 0.15 g of lithium bis(oxalato)borate was added to the dispersion, and the mixture was stirred at 800 rpm for 5 h at 60 °C under an argon atmosphere. After the reaction, the mixture was centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 90 °C for 6 h to obtain the modified boride.
[0148] S3: Preparation of supported lithium supplement.
[0149] Under a dry nitrogen atmosphere, the modified boride was added to anhydrous NMP and dispersed at 2000 rpm for 10 min to obtain a modified boride dispersion. The concentration of the modified boride dispersion was 1 mg / mL.
[0150] Under a dry nitrogen atmosphere, the lithium supplement was added to anhydrous NMP to obtain a suspension of the lithium supplement. The concentration of the lithium supplement suspension was 25 mg / mL.
[0151] Under stirring at 800 rpm, the modified boride dispersion was slowly added dropwise to the lithium supplement agent suspension, maintaining a mass ratio of modified boride to lithium supplement agent of 5:100. After the addition was complete, stirring was continued at 800 rpm for 30 min to obtain a supported lithium supplement agent slurry. In the obtained supported lithium supplement agent, the modified boride was discontinuously adsorbed onto the surface of the lithium supplement agent particles, with the coating rate of modified boride on the surface of a single lithium supplement agent particle being approximately 30%.
[0152] S4: Prepare modified cathode materials.
[0153] The NCM811 ternary cathode material was added to the above-mentioned supported lithium supplement slurry at a mass ratio of 50:10 to ternary cathode material and lithium supplement agent. Then, the mixture was stirred at a low speed of 600 rpm for 30 min under a dry nitrogen atmosphere to obtain the modified cathode material.
[0154] S5: Prepare the positive electrode sheet.
[0155] A modified cathode material, a conductive agent (CNT), a binder (PVDF), and a solvent (NMP) were mixed to obtain a cathode active slurry with a solid content of 70% and a viscosity of 7200 mPa·s. The mass ratio of the modified cathode material, the conductive agent, and the binder was 97.0:1.0:2.0.
[0156] The positive electrode active slurry was coated onto the surface of aluminum foil and dried sequentially at 65℃ for 5 min, 95℃ for 10 min, and 120℃ under vacuum for 8 h. Then, it was gently rolled at 80℃ and 180 N / cm to obtain the positive electrode sheet.
[0157] Comparative Example 1 The difference between this comparative example and Example 1 is that no supported lithium supplement was used to modify the cathode material. That is, the cathode material was not modified in any way.
[0158] Comparative Example 2 The difference between this comparative example and Example 1 is that only the cathode material is modified with a lithium supplement, that is, no modified boride is used.
[0159] Comparative Example 3 The difference between this comparative example and Example 1 is that only the cathode material is modified with modified boride, that is, no lithium supplement is used.
[0160] Comparative Example 4 The difference between this comparative example and Example 1 is that the two-dimensional metal boride was not modified by the lithium boron oxide modifier.
[0161] Comparative Example 5 The difference between this comparative example and Example 1 is that in the process of the supported lithium supplement, the dispersion of the modified boride and the suspension of the lithium supplement are mixed simultaneously.
[0162] Comparative Example 6 The difference between this comparative example and Example 1 is that the mass ratio of the lithium supplement to the modified boride is 100:0.2. Consequently, the coating rate of the modified boride on the surface of the lithium supplement is less than 5%.
[0163] Comparative Example 7 The mass ratio of lithium replenishing agent to modified boride is 100:10; correspondingly, the modified boride is continuously coated on the surface of the lithium replenishing agent.
[0164] Comparative Example 8 The difference between this comparative example and Example 1 is that the mass ratio of the positive electrode material to the lithium replenishing agent is 10:10.
[0165] Comparative Example 9 The difference between this comparative example and Example 1 is that the mass ratio of the positive electrode material to the lithium replenishing agent is 60:10.
[0166] Comparative Example 10 The difference between this comparative example and Example 1 is that the modified boride, lithium supplement, positive electrode material, conductive agent, binder and solvent are mixed at one time to prepare a positive electrode active slurry.
[0167] Test case Test conditions for full cells without negative electrode The positive electrode sheets obtained in each embodiment and comparative example were assembled with bare copper foil negative electrode current collectors to form a negative electrode-free lithium metal full cell. The cell structure consisted of a high-nickel ternary positive electrode and a bare Cu current collector, with no graphite, silicon-based negative electrode, lithium metal foil, or pre-deposited lithium layer on the negative electrode side, and an N / P ratio of 0. The separator was a PP / PE / PP composite separator, and the electrolyte was prepared from 30wt% DME, 50wt% LIFSI, and 20wt% TFEO.
[0168] During the initial charge, lithium ions are extracted from the positive electrode and deposited on the Cu current collector surface to form a metallic lithium layer. Subsequent cycles are achieved through lithium deposition / stripping on the Cu current collector. The test voltage range is 3.0V~4.3V, and the test temperature is 25℃. After two cycles of 0.05C formation, the battery is cycled using a 0.2C charge / 1C discharge cycle for a total of 60 cycles.
[0169] The test results are shown in Table 1.
[0170] Table 1 Test Results
[0171] As shown in Table 1, in the high-nickel ternary cathode to bare Cu electrodeless full cell system, Examples 1-8 generally exhibit better comprehensive electrochemical performance than Comparative Examples 1-8, indicating that the scheme provided in this application is beneficial to improving the lithium source compensation capability, interface stability and cycle performance in electrodeless lithium metal battery systems.
[0172] Comparing Comparative Example 1 with Example 1, it can be seen that although the uniform mixing of ordinary lithium supplementer Li5AlO4 can provide a certain amount of active lithium, the randomness of the contact between the lithium supplementer and the ternary cathode particles makes it difficult to ensure a stable and continuous electron transport path. As a result, some lithium supplementer cannot fully participate in the delithiation process, and the lithium supplementation utilization rate is limited. In contrast, Example 1, through pre-adsorption and secondary composite, enables the modified boride to localize and bridge Li5AlO4 with the ternary cathode particles, improving the continuity of electron contact around the lithium supplementer and making the delithiation and release process of Li5AlO4 more uniform, thereby improving the initial coulombic efficiency and cycle retention rate.
[0173] Comparing Comparative Examples 2-3 with Example 1, it can be seen that the absence of modified boride leads to a lack of effective interfacial bridging between the lithium replenisher and the ternary cathode material, resulting in limited improvement in electron transport capability and reduced lithium removal utilization of the lithium replenisher. The absence of lithium replenisher also leads to insufficient supply of active lithium on the cathode side during the first charging process, which cannot effectively compensate for the first irreversible lithium loss in the anode-free system, thus reducing the first coulombic efficiency and initial capacity.
[0174] Comparing Comparative Example 4 with Example 1, it can be seen that the two-dimensional metal boride, without the modification treatment of lithium boron oxide, will mainly exist as a normal two-dimensional conductive sheet and will not be able to form an interface bridging structure with lithium boron oxide end groups. Its interfacial bonding ability with the lithium replenishing agent and ternary cathode particles will decrease, resulting in a reduction in electron transport ability, lithium ion affinity and interfacial coordination stability, thereby limiting the improvement of lithium replenishing agent utilization.
[0175] Comparing Comparative Example 5 with Example 1, it can be seen that in the preparation process of the supported lithium supplement, if the modified boride dispersion and the lithium supplement suspension are directly mixed simultaneously, it is easy to cause preferential agglomeration between the two-dimensional metal boride sheets, which cannot form a uniform local pre-adsorption structure. As a result, the two-dimensional metal boride cannot be fully distributed on the surface of Li5AlO4, reducing the probability of forming an effective interface bridge with the ternary cathode material, and thus limiting the improvement effect of the lithium supplement electronic contact.
[0176] Comparing Comparative Examples 6-7 with Example 1, it can be seen that the mass ratio of lithium replenishing agent to modified boride needs to be controlled within a reasonable range. When the amount of modified boride is too low, there are insufficient effective bridging sites on the Li5AlO4 surface, limiting the improvement in electronic contact by the lithium replenishing agent. When the amount of modified boride is too high, it may cause an increase in localized coverage of the two-dimensional material on the lithium replenishing agent surface, reducing lithium-ion transport efficiency. Therefore, discontinuous localized bridging structures are more conducive to lithium replenishing agent release than continuous or excessively covered structures.
[0177] Comparing Comparative Examples 8-9 with Example 1, it can be seen that the content of the lithium replenishing agent Li5AlO4 in the modified cathode material also needs to be controlled. When the lithium replenishing agent content is too low, the available active lithium is insufficient and cannot fully compensate for the lithium loss in the anode-free system; when the lithium replenishing agent content is too high, although it can improve the lithium source supply during the first charging stage, excessive lithium replenishing agent may increase the side reactions at the cathode side interface and electrolyte consumption, leading to accelerated capacity decay during cycling.
[0178] Comparing Comparative Example 10 with Example 1, it can be seen that directly mixing Li5AlO4 and modified boride with the cathode material cannot fully utilize the interfacial bridging effect of the two-dimensional metal boride. The key reason is that a supported lithium supplement is not formed in advance, which makes it difficult for the two-dimensional metal boride to be localized between the lithium supplement and the ternary cathode particles, thereby reducing the utilization efficiency of the lithium supplement and the interface regulation effect.
[0179] In summary, this application pre-forms a supported lithium replenisher with modified boride and a lithium replenisher, and then combines it with the cathode material to form the cathode active material. On the one hand, Li5AlO4 releases active lithium during the first charge, compensating for the initial irreversible lithium loss in the anode-less system and improving the initial coulombic efficiency and initial capacity. On the other hand, the modified boride forms a localized bridge between the lithium replenisher and the ternary cathode particles, improving the electron contact conditions around the lithium replenisher and enhancing the uniformity of lithium release. Simultaneously, the aluminum-containing interface component formed after the lithium replenisher is delithiated, and the boron-containing, lithium-containing, and metal-oxygen bond-containing interface components induced by the modified boride, can synergistically stabilize the high-nickel ternary cathode interface, reducing electrolyte oxidation side reactions, interfacial impedance growth, and capacity decay during cycling.
[0180] Therefore, the proposed solution is particularly suitable for high-nickel ternary cathode-bare Cu-based full cell systems that require high lithium source compensation capability and interface stability.
[0181] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A modified boride, characterized in that, The modified boride is obtained by reacting a two-dimensional metal boride with a lithium boron oxide modifier at 40℃~70℃. The mass ratio of the two-dimensional metal boride to the lithium boron oxide modifier is 1:(0.01~0.3); The two-dimensional metal borides are two-dimensional sheet materials composed of transition metal elements and boron elements. The transition element M in the two-dimensional metal boride is Mo; the lithium boron oxide modifier is lithium bis(oxalato)borate.
2. The modified boride according to claim 1, characterized in that, The modified boride includes at least one of the following characteristics: Feature 1: The surface of the two-dimensional metal boride has at least one of surface end groups, intrinsic chemical bonds, and defect oxygen sites; wherein, the surface end groups include at least one of -O, -OH, and -F, the intrinsic chemical bonds include at least one of BO and MO, and the M in MO corresponds to the metal element in the two-dimensional metal boride; Feature 2: The modified boride surface has at least one of BO-Li, MO-Li, -O and -OH, where M in MO-Li corresponds to a metal element in a two-dimensional metal boride.
3. A method for preparing the modified boride as described in claim 1 or 2, characterized in that, Includes the following steps: Lithium boron oxide modifier was added to a two-dimensional metal boride dispersion and reacted at 40℃~70℃ under a protective atmosphere for 4h~8h.
4. The preparation method according to claim 3, characterized in that, The two-dimensional metal boride was mixed with a solvent at a solid-liquid ratio of 0.5 mg:1 mL to 2 mg:1 mL, and then dispersed to obtain the two-dimensional metal boride dispersion.
5. A supported lithium supplement, characterized in that, Formed from a lithium supplement and the modified boride as described in claim 1; The modified boride has a coating rate of 5% to 40% on the surface of the lithium supplement.
6. A method for preparing the supported lithium supplement as described in claim 5, characterized in that, Includes the following steps: The dispersion of the modified boride was added dropwise to the suspension of the lithium supplement, followed by stirring; The mass ratio of the lithium supplement to the modified boride is 100:0.5 to 100:
5.
7. A method for preparing the supported lithium supplement as described in claim 5, characterized in that, Includes the following steps: The lithium replenishing agent and the modified boride were dry mechanically fused in a dry environment with a dew point below -40°C. The mass ratio of the lithium supplement to the modified boride is 100:0.5 to 100:
5.
8. A modified cathode material, characterized in that, The modified cathode material is prepared by using a cathode material and the supported lithium supplement agent as described in claim 5.
9. A positive electrode sheet, characterized in that, The positive electrode sheet contains the modified positive electrode material as described in claim 8.
10. A negative electrode-free lithium metal battery, characterized in that, Includes the positive electrode sheet as described in claim 9.
